The Concept of Empowering Students in Islamic Boarding Schools - Khomsatun; Wachid Bambang Suharto, Abdul; Supriyanto (International Proceedings of Nusantara Raya, 2022)
Santri and Pondok Pesatren are wadas and interrelated contents. Students who are also students are persistent warriors of knowledge in receiving education in the form of religious education and general education. Therefore, this research will explain and elaborate on the concept of empowering students in Islamic boarding schools. This research uses qualitative research method method. The research technique or approach implemented in this research is with library research, which utilizes written objects in the form of books, journals that discuss related topics studied. Data analysis in the decipherment of concepts in this study, also applied approaches or types of reflective conceptual research, or the application of gagagasan that have previously been explored by researchers by adjusting adjustments to conditions and situations related to the object of study. In relation to the object of research, researchers explore issues related to the concept of empowering students in Islamic boarding schools. From the solution of these problems, later researchers will describe in the discussion section related to concepts that are parsed based on experience in the field. The results and discussions related to the concept of empowerment that will be described in the discussion are the concept of empowerment that is oriented towards economic, skill, and health aspects.